The Role of Multimodal Stimuli in Violin Learning: A Literature Review on the Effectiveness of Visual, Auditory, and Haptic Modalities as Pedagogical Strategies - Hapsari, Maria Magdalena Cita; Wadiyo, Wadiyo; Haryono, Slamet (Riwayat: Educational Journal of History and Humanities, 2025)
Violin learning presents its own set of challenges, particularly in developing students fundamental techniques and musical sensitivity, which require refined motor coordination and heightened auditory perception. The observed low effectiveness of conventional violin instructionoften centered on verbal guidance and repetition without sufficient sensory supporthighlights the need for more innovative pedagogical approaches. This study aims to investigate the role of stimuli in violin learning through a comprehensive academic literature review, with a specific focus on visual, auditory, and haptic modalities. The research adopts a qualitative literature review method, drawing from peer-reviewed journal articles published between 2015 and 2025. Findings indicate that the application of multimodal stimuli significantly enhances technical accuracy, accelerates the learning process, and boosts student motivation and engagement. These results underscore that stimuli function not merely as supplementary tools, but as essential components in effective violin teaching strategies that are responsive to students diverse learning needs.